Classical and fluctuation‐induced electromagnetic interactions in micron‐scale systems: designer bonding, antibonding, and Casimir forces. Issue 1 (6th November 2014) - Rodriguez, Alejandro W.; Hui, Pui‐Chuen; Woolf, David P.; Johnson, Steven G.; Lončar, Marko; Capasso, Federico; Harris, Jack; Rabl, Peter; Schliesser, Albert
<x xml:space="preserve">Abstract</x> Whether intentionally introduced to exert control over particles and macroscopic objects or whether arising from quantum fluctuations of charges, electromagnetic interactions play a fundamental role in many naturally occurring processes and technologies. Although these effects arise from exchange of electromagnetic momentum, their dramatically different origins, involving either real or virtual photons, lead to different physicalmanifestations. This review describes recent experimental and theoretical progress in understanding and designing optomechanical and quantum‐fluctuation forces between micronscale bodies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>